(untitled) (Research, Society and Development, 2023)
Congenital heart diseases (CHD) represent an important cause of morbidity and mortality, accounting for approximately 8% of infant mortality. Of these, approximately 30% of deaths occur in the early neonatal period. They are defined as abnormalities in the cardiocirculatory structure and function, present from birth, caused by changes in the embryonic development of the heart. They may occur due to genetic, environmental or idiopathic factors and are classified as cyanotic and acyanotic. This present study aims to carry out a narrative literature review on the clinical management of cyanotic congenital heart diseases. Articles from the Pubmed, Scielo and Google Scholar platforms were analyzed, using descriptors such as: congenital heart disease, cyanosis and newborn. The studies evaluated showed the importance of early diagnosis of cyanotic CHD, which can be performed during pregnancy, through fetal or even postnatal echocardiography. It was observed that from the suspicion or confirmation of this comorbidity, it is essential to institute the appropriate clinical management of this newborn. Because, when treatment is instituted early, it has contributed to increase the survival of these children.